Interpretative SOL modeling throughout multiple ELM cycles in DIII-D. (March 2021) - Nelson, A.O.; Xing, Z.A.; Izacard, O.; Laggner, F.M.; Kolemen, E.
Abstract: Coupling between the UEDGE (edge fluid model), GINGRED (grid generation) and CAKE (equilibrium reconstruction) codes opens the door for automated interpretative scrape-off-layer (SOL) analysis over entire discharges, providing information that is essential in efforts to couple the SOL to core transport codes. In this work, we utilize new developments in the autoUEDGE code (Izacard et al. 2018) to investigate the behavior of the DIII-D SOL during the temporal evolution of an edge-localized mode (ELM) cycle. Modeled temperature and density profiles in UEDGE are automatically matched to experimental measurements by iteratively and self-consistently adjusting transport coefficient profiles in the plasma edge. This analysis is completed over multiple ELM cycles of a well-diagnosed discharge with long ( ∼ 100 ms ) inter-ELM periods. Directly after the ELM crash, a short period of high-density, low-temperature conditions is observed in Langmuir probe measurements at the outer divertor. This regime is associated with enhanced D α emission and incident particle flux, suggesting that the divertor enters a period of high recycling after an ELM crash. After about ∼ 25 ms, divertor conditions return to their pre-ELM conditions and remain there for several tens of milliseconds. Using the autoUEDGE code, the SOL is modeled as a function of ELM cycle using upstream profiles as input. The 2D modeling successfully reproduces both divertor Thomson scattering measurements and the experimentally observed divertor dynamics. Though the recycling is kept fixed throughout the modeling, changes in particle fluxes are consistent with local experimental recycling changes induced by ELMs. Agreement between modeling and observation suggests a strong link between upstream profiles and the high-recycling divertor conditions directly following large type-I ELMs. Highlights: An extended period of increased density is achieved post-ELM in the DIII-D divertor. A code is developed to automatically converge interpretative UEDGE runs. 2D models reproduce experimental divertor behavior as a function of ELM cycle. Inter-ELM divertor behavior is closely linked to upstream profile evolution.